Synthesis of anhydrous manganese hypophosphite microtubes for simultaneous flame retardant and mechanical enhancement on poly(lactic acid). (18th August 2018) - Yang, Wei; Yang, Wen-Jie; Tawiah, Benjamin; Zhang, Yang; Wang, Li-Li; Zhu, San-E; Chen, Timothy Bo Yuan; Yuen, Anthony Chun Yin; Yu, Bin; Liu, Yun-Feng; Si, Jing-Yu; Hu, En-Zhu; et al.
Abstract: In this study, a facile solvothermal approach for preparing anhydrous manganese hypophosphite (A-MnHP) microtubes was demonstrated for the first time by using manganese chloride and hypophosphorous acid in mixed solvents, followed by fabricating A-MnHP-based poly(lactic acid) (PLA) composites via a melt-blending method. Owing to the unique morphology of A-MnHP, the tensile strengths of the PLA composites with 1 wt%, 5 wt% and 10 wt% A-MnHP are approximately 17%, 7% and 3% higher than those of neat PLA, respectively. Compared to neat PLA, PLA composite containing 15 wt% A-MnHP (PLA/A-MnHP15) exhibited lower peak heat release rate (50% reduction), total heat release (13% reduction), peak CO2 and CO productions (50% and 53% reductions), which also passed UL 94 V-2 rating test with high limiting oxygen index (27.5%). The combustion temperature change during the cone calorimeter tests showed that PLA/A-MnHP15 showed the lowest combustion temperature, achieving the best fire safety performance. Residue analysis indicated that the presence of A-MnHP resulted in the formation of continuous and compact char residues composed of aromatic structure and phosphorous-rich inorganic structure, retarding the permeation of heat, oxygen transfer and escape of volatile degradation products. Graphical abstract: Image 1